118 Applying appropriate use criteria for transthoracic echocardiography to clinical practice. (5th June 2017) - Robbins, Zach; Burgess, Malcolm; Harrison, Ben
Abstract : Introduction: Transthoracic echocardiography (TTE) is a well-established, non-invasive method of investigating multiple pathologies in cardiology and is widely accessible to non-cardiologists. Appropriateness use criteria (AUC) have been developed by the American College of Cardiology Foundation (ACCF), but these are not implemented systematically in everyday practice. Previous studies indicate that approximately 1 in 10 requests may be avoidable. In our hospital the cardiorespiratory department performs over 10, 000 TTEs per year. While most requests for TTE are appropriate, a small number of inappropriate requests amounts to an avoidable burden in the workload of department. Purpose: To determine how many inappropriate requests were received by the department and if there were any patterns to the inappropriate requests that would inform the development of screening questions when moving from a paper based to electronic requesting system. Methods: All inpatient and outpatient requests were collected and analysed over 12 consecutive days in January 2015. The system for requesting TTEs was paper based with free text boxes. Requests from primary care were excluded as they had fixed criteria for requesting TTEs. All requests were assigned to the most closely applicable indication and appropriateness score based on the ACCF 2011 criteria. The requesting system was then changed to an electronic system with mandatory screening questions based on the AUC. All inpatient and outpatient requests were again collected over 14 consecutive days, in August/September 2016, once the electronic system was established. Requests were analysed using the same criteria. Results: We analysed 294 requests, 2.4 outpatient requests for each inpatient request, in 2015 and 333 requests, 1.85 outpatient requests for each inpatient request, in 2016. Approximately half of requests came from cardiology services, 47% in 2015 and 52% in 2016. The commonest indications were similar both years, with ACCF indications 1 and 2; symptoms (e.g. chest pain, palpitations, dyspnoea, etc.) or test results suggesting cardiac pathology (e.g. abnormal ECG, elevated cardiac biomarkers, etc.) accounting for 22% of requests in 2015 and 34% in 2016. In 2015, 91% (n=266) of requests were appropriate, 5% (n=16) of uncertain appropriateness and 4% were inappropriate (n=12). After implementation of the screening questions through electronic requesting, inappropriate requests had reduced to 1% (n=4) of total requests, 2% (n=5) were of uncertain appropriateness and 97% (n=324) were appropriate (p=0.0477). This equated to an estimated reduction of eight inappropriate or uncertain requests a week. Conclusion: After implementation of screening questions in an electronic requesting system, inappropriate requests fell. Systematic screening of TTE requests can help to reduce inappropriate requests and allow resources to be focused on appropriate indications.